Pilot Study of the Effects of Paced Breathing on Measures of Convergent and Divergent Thinking. Issue 1 (3rd March 2023) - Wallace, McKenzie B.; Costa, Amy N.; Ferguson, Bradley J.; Carey, Megan A.; Rzeppa, Chloe; Kille, Briana M.; Drysdale, David R.; Sutton, Briann E.; Shuler, Brianne H.; Johnson, Ryan P.; Kwenda, Elizabeth P.; Hadley, Jamie; et al.
Abstract : Background: The ability of the autonomic nervous system's stress response to impair aspects of cognitive flexibility is known. However, the ability to modulate the sympathetic response and improve these cognitive impairments via nonpharmacological intervention, such as paced breathing (PB), requires further investigation. Objective: To better elucidate the effects of PB on cognition. Method: We employed a PB protocol in a total of 52 healthy men and women and measured performance on convergent and divergent cognitive tasks, perceived stress, and physiological measures (eg, blood pressure, heart rate). Participants attended two experimental sessions consisting of either PB or normal breathing followed by cognitive assessments including convergent (compound remote associate, anagram) and divergent (alternate use, fluency) tasks. Experiment 2 consisted of more difficult versions of cognitive tasks compared with Experiment 1. Results: In Experiment 1, PB significantly reduced the female participants' systolic and diastolic blood pressure immediately after the breathing protocol without affecting their cognition. In Experiment 2, PB significantly reduced perceived stress immediately after the breathing protocol, regardless of sex. There was no effect on cognition in Experiment 2, but a correlation was observed between perceived stress change and anagram number solved change. Conclusion: While PB modulates sympathetic activity in females, there was a lack of improvement in cognitive flexibility performance. At least for a single trial of PB, cognitive flexibility did not improve.